Correlation Between Histopathology and Fnac in Thyroid Lesion Diagnosis - Muhammad Hafeez, Aurangzaib Khan, Mohibullah Khan, Mansoor Alam, Siyab Ahmad, Shabir Ahmed Orakzai (Pakistan Journal of Medical & Health Sciences, 2022)
Background: FNAC is effective for the identification of benign and malignant thyroid lesions prior to surgery or therapy, which helps to limit the number of needless treatments. Thyroid swelling FNAC is a straightforward, quick, patient-friendly, and low-cost technique that may be repeated if samples are insufficient. It has the highest predictive value of any diagnostic method presently available. Objective: To confirm if the fine needle aspiration cytology (FNAC) and histopathology have any correlation in the diagnosis of thyroid lesions. Place and duration of research: The present study comprised 100 patients in the ENT department, Khyber teaching hospital from January 2019 to December 2020. Materials and Methods: Multiple neck swellings were presented to the ENT department in Khyber teaching hospital where they were clinically assessed after a thorough history was gathered. FNAC was administered to just those thyroid-swelling patients who were hospitalized to an indoor facility and ultimately had surgery, according to the findings of this study. Every patient had a preoperative FNAC as well as a postoperative histopathology report of thyroid lesions. Before each of the 100 surgeries, informed consent was obtained. Results: The histopathological diagnosis of thyroid lesions was associated with the FNAC diagnostic. There were 26 men and 78 women among the 104 patients. The male-to-female ratio was 1:3. The majority of the 104 patients were between the ages of 31 and 40. There were 9 false Cyto-diagnosis cases out of 104 FNAC patients. The overall accuracy rate was 91.35%. Conclusion: As a preoperative examination of thyroid gland swelling before surgery, FNAC is a reliable, safe, and somewhat accurate approach. FNAC is a reliable diagnostic test for evaluating thyroid swelling since it is more accurate in diagnosing thyroid gland cancer.